GENDER CORRELATION BETWEEN COMPLIANCE AND THE HEALTH PROTOCOL IN THE NEW NORMAL ERA (THE CASE ON STUDENTS IN PEKANBARU) - Tantri Puspita Yazid; Irwan Iskandar; Salsabila Salsabila; Oktri Permata Lani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
Facing Covid-19, the government responded with a new normal policy. The public must implement the 5M health protocol to break the chain of the spread of Covid-19, such as wearing masks, washing hands, maintaining distance, staying away from crowds, and limiting mobility. Through the policy, a compliance action can be investigated. speaking about gender, gender differences seem to influence the health behavior of men and women. According to White, gender is a description of the behavior patterns of men or women which recognized in social life. This study aimed to determine the correlation between gender and compliance with health protocols in the New Normal Era. The population in this study were all students studying at the top 5 universities in Riau Province using the Propionate Stratified Random Sampling technique. The method used is a quantitative method with data collection techniques using questionnaires and observation. In this study using construct validity (construct validity). Testing the validity of this research instrument was carried out with the help of the SPSS 25 application/software and using the Pearson bivariate technique. Meanwhile, the instrument reliability test in this study used the Cronbach Alpha Formula technique and the SPSS 25 in windows program. The data were analyzed using the SPSS Spearman's Rank test, which states the correlation between X and Y variables. The results obtained by this study indicate a significant correlation between the Gender variable and the Health Protocol Compliance variable.